2016
DOI: 10.1017/s1751731115002943
|View full text |Cite
|
Sign up to set email alerts
|

Genomic inbreeding estimation in small populations: evaluation of runs of homozygosity in three local dairy cattle breeds

Abstract: In the local breeds with small population size, one of the most important problems is the increase of inbreeding coefficient ( F). High levels of inbreeding lead to reduced genetic diversity and inbreeding depression. The availability of high-density single nucleotide polymorphism (SNP) arrays has facilitated the quantification of F by genomic markers in farm animals. Runs of homozygosity (ROH) are contiguous lengths of homozygous genotypes and represent an estimate of the degree of autozygosity at genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
128
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(181 citation statements)
references
References 42 publications
38
128
5
2
Order By: Relevance
“…Therefore two further estimates of genomic inbreeding, F GRM and F HOM, were used to evaluate the efficacy of F ROH as a measure of inbreeding in sheep populations. The strong correlation between F ROH1Mb and F HOM in the present study corroborates previous results found in cattle [7, 63], although the correlation between F ROH and F GRM was greater than those previously estimated [7, 60, 63]. Both measures, F GRM and F HOM, have been previously shown to be strongly dependent on allele frequencies, particularly for populations with divergent allele frequencies, which can lead to misleading IBD results [7].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore two further estimates of genomic inbreeding, F GRM and F HOM, were used to evaluate the efficacy of F ROH as a measure of inbreeding in sheep populations. The strong correlation between F ROH1Mb and F HOM in the present study corroborates previous results found in cattle [7, 63], although the correlation between F ROH and F GRM was greater than those previously estimated [7, 60, 63]. Both measures, F GRM and F HOM, have been previously shown to be strongly dependent on allele frequencies, particularly for populations with divergent allele frequencies, which can lead to misleading IBD results [7].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, although most of the ROH detected in Barbaresca were in the shorter length categories (1 to 10 Mb), as also reported in studies of cattle populations (Mastrangelo et al, 2016), the individuals showed a total length of ROH characterized by the presence of large segments (23% of ROH > 10 Mb). In general, estimates of ROH are rare in local breeds, and to the best of our knowledge, few studies have been conducted in sheep.…”
Section: Discussionsupporting
confidence: 78%
“…The most extreme animal exhibited an ROH genome coverage encompassing 786.84 Mb of the total autosomal genome extension (UMD3.1) covered by markers (31.47% of the cattle genome). Similar results were described in several cattle breeds, whose findings reported a coverage varying from 25% to 29.20% of the cattle genome (Marras et al, 2015;Mastrangelo et al, 2016;Peripolli, Metzger, et al, 2018;Purfield et al, 2012;Szmatoła et al, 2016).…”
Section: Distribution Of Rohsupporting
confidence: 87%
“…The number of ROH per chromosome was greater for BTA5 (532 segments) and the greater fraction of chromosome covered with ROH was found on BTA25 (16.91% of chromosomal length within an ROH; Figure ). Our previous studies in indicine cattle (Peripolli, Metzger, et al, ; Peripolli, Stafuzza, et al, ) also have described the greatest number of ROH on BTA5, whereas others have found on BTA1 (Gurgul et al, ; Mastrangelo et al, ; Purfield et al, ).…”
Section: Resultsmentioning
confidence: 84%